2021
DOI: 10.1111/dom.14360
|View full text |Cite
|
Sign up to set email alerts
|

Applying REWIND cardiovascular disease criteria to SUSTAIN 6 and PIONEER 6: An exploratory analysis of cardiovascular outcomes with semaglutide

Abstract: In the REWIND trial, dulaglutide reduced cardiovascular (CV) risk versus placebo in patients with type 2 diabetes in both the "established CV disease" (CVD) and "CV risk factor" subgroups. The SUSTAIN 6 and PIONEER 6 trials of semaglutide used different criteria for established CVD from those used in REWIND. The present post

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Our findings align with the literature evidence supporting the prominent place of semaglutide in treating T2D patients at high CV risk [12,26,37]. Indeed, data from various clinical trials highlighted the effectiveness of this treatment even compared with other GLP-1 agonists [14,15,38,39].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings align with the literature evidence supporting the prominent place of semaglutide in treating T2D patients at high CV risk [12,26,37]. Indeed, data from various clinical trials highlighted the effectiveness of this treatment even compared with other GLP-1 agonists [14,15,38,39].…”
Section: Discussionsupporting
confidence: 91%
“…Semaglutide reduced MACE in people with T2D at a high risk of CV disease in the SUSTAIN 6 trial, resulting in improved CV risk factors and increased life-years of the patients who practiced this therapy as an add-on to their practiced hypoglycemic therapy; this was probably due to the underlying CV risk of these patients and the time of initiation of treatment with semaglutide [10,16,25,26]. This 4-month retrospective, real-world study of T2D patients showed that injectable semaglutide significantly reduced HbA1c levels and cIMT, supporting the effect of this treatment on subclinical atherosclerosis as previously shown for some but not all GLP-1RAs [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…However, the REWIND (dulaglutide) trial used different criteria for CVD than SUS-TAIN and PIONEER (semaglutide) [6]. Nevertheless, a pooled posthoc analysis of SUSTAIN-6 and PIONEER-6 trials using the REWIND CVD criteria suggested that semaglutide may also be extended to patients with type 2 diabetes across the CV risk continuum, consistent with dulaglutide results from REWIND [7]. Thus, GLP-1RA could be considered in people with type 2 diabetes with either previous CVD or cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 77%